Families Can Do Coping: Parenting Skills in the Early Years. (21st May 2014) - Frydenberg, Erica; Deans, Jan; Liang, Rachel
<x content-type="archive" xml:space="preserve">Abstract</x> Parenting programmes are very much a part of the international landscape in Western communities. Coping skills provide a useful resource for parents and children in managing their everyday lives, both together and individually. Following a 5-year research programme with parents and children in an early years setting, Families Can Do Coping was developed as a comprehensive parenting skills programme that incorporates parents' understanding of their own coping and that of their children. The programme was delivered with the twin aims of teaching communication and coping skills to parents. In 2012, five 2-hour sessions were delivered to 19 parents in an Early Learning Centre at the University of Melbourne. The five-session programme focused on providing parents with information regarding coping skills and the use of visual tools to assist parents to engage with their children in conversations about coping. Additionally, parents completed a pencil-and-paper coping skills evaluation for their child. The programme outcomes included perceptions of parents' enhancement of their wellbeing, and development of proactive and productive coping skills in both parents and children. After a 3-month period three parents provided feedback on their progress and use of the new tools and strategies for maintaining helpful parenting.